Metode Rapid Application Development Pada Penerapan Pemesanan Tiket Online Gunung Slamet Berbasis Website - Abdurahman; Harahap, Muhammad Aldho Febrian; Zen, Bita Parga; Firdaus, Eryan Ahmad; Kisworini, Rianti Yunita (Jurnal Informatika, 2024)
This research aims to design a website-based online ticket booking system for climbing Mount Slamet via Dipajaya, Central Java. The current manual registration system poses issues such as time-consuming on-site registration and inefficient data management of hikers' information, including identities, hiking dates, and group sizes. Additionally, the inspection of hikers' belongings, which may contribute to waste, is not optimally conducted due to limited personnel. The Rapid Application Development (RAD) method is employed to support the information system design, combining structured techniques, prototyping, and joint application development to expedite system development. The outcome of this research is the design of an eticketing and information system that enables hikers to conveniently book tickets online without queuing or visiting the location in person, thus facilitating data management and analysis for future service enhancement. The discussion encompasses system development processes, user requirements analysis, interface design, and system testing. In conclusion, the web-based e-ticketing and information system enhance ticket management efficiency and provide convenience for visitors to book tickets online, with potential for further service improvements in the future.